Determinants of Excess and Deficit Cash Holdings of Firms: Evidence from Emerging Market. Issue 5 (October 2021) - Das, Santanu; Goel, Utkarsh
Using a sample of Indian firms, we study the determinants of corporate cash holdings in an emerging economy. We study the excess and deficit cash holdings and assess the impact of leverage, accrual quality and working capital accruals on cash holdings. We find that after controlling for growth and size, leverage depends upon whether the firm holds excess or deficit cash. Levered firms with high profitability (measured via return on equity—ROE) hold less cash as compared to firms holding less than desired cash even if the profitability is high, and ample growth opportunities are available. We also find that while operating profit has no significant impact on cash holdings, volatility of sales does have a positive and significant impact. Firms having ready access to capital market (proxied by size and amount of leverage) are less likely to hold cash. Therefore, we argue that such firms can focus on value-generating activities without having to worry about liquidity. At the same time, smaller firms with good profitability (measured as return to equity) may also hold less cash as presented in this study.